2005
DOI: 10.1158/0008-5472.can-05-2580
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Inactivation of the Receptor Tyrosine Kinase EPHB2 in Colorectal Tumors

Abstract: The receptor tyrosine kinase EPHB2 has recently been shown to be a direct transcriptional target of TCF/B-catenin. Premalignant lesions of the colon express high levels of EPHB2 but the expression of this kinase is reduced or lost in most colorectal carcinomas. In addition, inactivation of EPHB2 has been shown to accelerate tumorigenesis initiated by APC mutation in the colon and rectum. In this study, we investigated the molecular mechanisms responsible for the inactivation of EPHB2 in colorectal tumors. We s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
83
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 13 publications
5
83
0
Order By: Relevance
“…We observed EPHB2 LOH in 25% (3/12) and promoter hypermethylation in 63% (5/8) of serrated tumors. Our study on EPHB2 inactivation in CRC (Alazzouzi et al, 2005) has showed that EPHB2 promotor methylation indeed is causally related to the reduced expression of EPHB2 protein in a cell line and we found frequent frameshift mutations in EPHB2 in MSI adenomas and carcinomas (21 and 41%, respectively). This finding is interesting and well compatible with our present data on serrated CRCs; indeed, previous literature (Hawkins and Ward, 2001;Ma¨kinen et al, 2001) has connected MSI phenotype and serrated morphology, and early loss of EPHB2 may play a role in this association.…”
Section: Molecular Classification Of Serrated Crc P Laiho Et Alsupporting
confidence: 53%
“…We observed EPHB2 LOH in 25% (3/12) and promoter hypermethylation in 63% (5/8) of serrated tumors. Our study on EPHB2 inactivation in CRC (Alazzouzi et al, 2005) has showed that EPHB2 promotor methylation indeed is causally related to the reduced expression of EPHB2 protein in a cell line and we found frequent frameshift mutations in EPHB2 in MSI adenomas and carcinomas (21 and 41%, respectively). This finding is interesting and well compatible with our present data on serrated CRCs; indeed, previous literature (Hawkins and Ward, 2001;Ma¨kinen et al, 2001) has connected MSI phenotype and serrated morphology, and early loss of EPHB2 may play a role in this association.…”
Section: Molecular Classification Of Serrated Crc P Laiho Et Alsupporting
confidence: 53%
“…c-Myc may be amplified in some cases, and cyclinD1 in a very few. EPHB2 undergoes slippage in a short repeat tract in about half of microsatellite-unstable colon cancers (Alazzouzi et al, 2005), although biallelic changes are apparently uncommon; other tumours show transcriptional silencing. The functional consequences, if any, of these EPHB2 changes are currently unknown.…”
Section: Other Genetic Changes That Affect Wnt Signallingmentioning
confidence: 99%
“…Overexpression of EphB2, ephrinB1, EphA2, and ephrinA1 has been reported in gastric cancer [11][12][13] . On the other hand, the concept that Eph receptors are oncogenes needs a new look on the basis of recent findings of downregulation of Eph receptors in certain types of cancer [14][15][16][17] . However, because functions of Eph receptors can overlap, loss of one receptor can be partially compensated for by other Eph receptors that have similar ligand-binding specificities and expression patterns [7] .…”
mentioning
confidence: 99%